2012
DOI: 10.4018/ijepr.2012040104
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of Electronic Planning within Planning Reform

Abstract: The limited research on e-Planning in Australia, a perceived slow take up of e-Planning in the New South Wales (NSW) planning system, and the release of a set of e-Planning recommendations as part of a larger planning reform package in November 2007 are the three main reasons for conducting this research. The goal of this paper is to discover the attitudes of planners in the NSW planning system toward Information Technology, and secondly, what the planners understanding of the e-Planning recommendations are. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Although PSS have been available for more than two decades, their adoption by planners is rather low. Indeed, it has been shown that instrumental, human, organisational and institutional factors, such as low instrument quality, low awareness by planners and low diffusion to and within planning organisations, hamper the adoption of PSS [Russo et al 2017;Brömmelstroet 2013;Williamson & McFarland 2012;Vonk & Geertman 2008;Klosterman & Pettit 2005]. Geertman [2017] recently analysed PSS from four perspectives, namely PSS history, PSS research, PSS education and PSS in practice, and encouraged to differentiate research on PSS in order to improve the body of knowledge and possibly PSS adoption in practice.…”
Section: Related Workmentioning
confidence: 99%
“…Although PSS have been available for more than two decades, their adoption by planners is rather low. Indeed, it has been shown that instrumental, human, organisational and institutional factors, such as low instrument quality, low awareness by planners and low diffusion to and within planning organisations, hamper the adoption of PSS [Russo et al 2017;Brömmelstroet 2013;Williamson & McFarland 2012;Vonk & Geertman 2008;Klosterman & Pettit 2005]. Geertman [2017] recently analysed PSS from four perspectives, namely PSS history, PSS research, PSS education and PSS in practice, and encouraged to differentiate research on PSS in order to improve the body of knowledge and possibly PSS adoption in practice.…”
Section: Related Workmentioning
confidence: 99%
“…In the broader sense e-planning is a socio-cultural, ethical and political practice, in which people take part in the subsequent phases of the planning process, both directly (offline) and remotely (online) (Horelli & Wallin, 2010). Since it is obvious that planners' are supportive of using ICT in their workplace and that they recognise the benefits of electronic communications, simultaneously they prefer the face-to-face contact to communicate complex issues (Williamson & McFarland, 2012). This broad view captures all the contemporary forms of decision-making processes, however it does not explain in what sense e-planning is different from traditional planning.…”
Section: E-planning and Its Characteristicsmentioning
confidence: 99%
“…In the broader sense EP is a socio-cultural, ethical and political practice, in which people take part in the subsequent phases of the planning process, both directly (offline) and remotely (online) (Horelli & Wallin, 2010). Since it is obvious that planners are supportive of using ICT in their workplace and that they recognise the benefits of electronic communications, simultaneously they prefer the face-to-face contact to communicate complex issues (Williamson & McFarland, 2012). This broad view captures all the contemporary forms of decision-making processes, however it does not explain in what EP is different from traditional planning.…”
Section: E-planning and Its Valuesmentioning
confidence: 99%